2018
DOI: 10.1128/jvi.00701-18
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Attenuation by Codon Pair Deoptimization Induces Sterilizing Immunity in Mouse Models

Abstract: Zika virus (ZIKV) infection during the large epidemics in the Americas is related to congenital abnormities or fetal demise. To date, there is no vaccine, antiviral drug, or other modality available to prevent or treat Zika virus infection. Here we designed novel live attenuated ZIKV vaccine candidates using a codon pair deoptimization strategy. Three codon pair-deoptimized ZIKVs (Min E, Min NS1, and Min E+NS1) were synthesized and recovered by reverse genetics and contained large amounts of underrepresented c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 66 publications
(116 reference statements)
1
53
1
Order By: Relevance
“…This is intriguing as the ribosome travels through the entire ORF thereby encountering individual segments of codon pair deoptimized sequences. Unlike the loss of protein expression observed in CPD Influenza viruses [ 24 , 29 ] or reduced protein expression in a codon pair deoptimized poliovirus variant [ 49 ]we do not have evidence of specific loss of recoded protein expression in DENV2 syn infected cells. Importantly, neither decreased temperature ( Fig 5 ), nor addition of innate immune inhibitor TBK-1 (not shown), nor addition of Jak Inhibitor I [ 17 ] completely rescued replication of the deoptimized DENV variants.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This is intriguing as the ribosome travels through the entire ORF thereby encountering individual segments of codon pair deoptimized sequences. Unlike the loss of protein expression observed in CPD Influenza viruses [ 24 , 29 ] or reduced protein expression in a codon pair deoptimized poliovirus variant [ 49 ]we do not have evidence of specific loss of recoded protein expression in DENV2 syn infected cells. Importantly, neither decreased temperature ( Fig 5 ), nor addition of innate immune inhibitor TBK-1 (not shown), nor addition of Jak Inhibitor I [ 17 ] completely rescued replication of the deoptimized DENV variants.…”
Section: Discussioncontrasting
confidence: 82%
“…Since then, we have initiated research into CHIKV and ZIKV. Our CPD approach for attenuating flaviviruses is being independently pursued for Yellow Fever virus [ 48 ] and Zika virus[ 49 ]. Although this work is limited to DENV2 16681, we hope to extend our method of selective deoptimization to the other three DENV serotypes, and to other mosquito-borne viruses including emerging or re-emerging threats such as Zika virus [ 50 ], yellow fever virus, and chikungunya virus [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only codon usage, but also codon-pair frequencies can affect PV fitness. It has been suggested that viruses deoptimized for codon pairs may open the way to a new generation of antiviral vaccines (Coleman et al, 2008), and this approach is currently investigated with other viral systems [(Martrus et al, 2013;Le Nouen et al, 2014;Nogales et al, 2014;Cheng et al, 2015;Li et al, 2018), among other investigations]. These observations reflect once again the multiple ways in which a viral RNA per se can be part of the viral phenotype, independently of its protein-coding function.…”
Section: Codon Usage As a Selective Constraint: Virus Attenuation Thrmentioning
confidence: 99%
“…This approach offers the theoretical advantage of avoiding exogenous immunosuppression, but at the expense of preventing the assessment of vaccine performance against transplacental transmission. As an alternative to a transient type I IFN blockade, in an experiment with a limited number of animals, females deficient in both type I and II IFN receptor signaling ( Ifnar1 −/− Ifngr1 −/− ) were utilized to evaluate a codon pair deoptimized LAV ZIKV vaccine [ 50 ]. Pregnant Ifnar1 −/− Ifngr1 −/− dams were challenged with ZIKV six days after mating to Ifnar1 −/− Ifngr1 −/− sires, which resulted in 100% of unvaccinated dams succumbing prior to delivery, whereas all immunized dams gave birth to healthy-appearing pups.…”
Section: Development Of Zikv Countermeasures In Pregnant Micementioning
confidence: 99%